Analisis Pengendalian Internal Terhadap Persediaan Obat Farmasi Pada Pusat Kesehatan Masyarakat (Puskesmas) (Studi Kasus Puskesmas Selong) - Rofiq Notonegoro; Bambang (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to assess the effectiveness of internal control of drug supply at the Selong Community Health Center using the COSO framework. The method used is descriptive quantitative through questionnaires, with interviews and observations as supplementary data. Analysis was conducted using a percentage formula to determine the effectiveness of each component. The results show that the control environment, control activities, information and communication, and monitoring are in the very good category. Meanwhile, risk assessment is in the good category because the use of technology is not optimal. Internal communication runs smoothly, but digital recording is still limited to a combination of manual and electronic. Overall, internal control at the Selong Community Health Center is running effectively, although improvements in information technology and physical supervision are still needed.